[Re]considering Respect for Persons in a Globalizing World. Issue 2 (11th April 2014) - Padela, Aasim I.; Malik, Aisha Y.; Curlin, Farr; De Vries, Raymond
Abstract Contemporary clinical ethics was founded on principlism, and the four principles: respect for autonomy, nonmaleficence, beneficence and justice, remain dominant in medical ethics discourse and practice. These principles are held to be expansive enough to provide the basis for the ethical practice of medicine across cultures. Although principlism remains subject to critique and revision, the four‐principle model continues to be taught and applied across the world. As the practice of medicine globalizes, it remains critical to examine the extent to which both the four‐principle framework, and individual principles among the four, suffice patients and practitioners in different social and cultural contexts. Using the four‐principle model we analyze two accounts of surrogate decision making – one from the developed and one from the developing world – in which the clinician undertakes medical decision‐making with apparently little input from the patient and/or family. The purpose of this analysis is to highlight challenges in assessing ethical behaviour according to the principlist model. We next describe cultural expectations and mores that inform both patient and clinician behaviors in these scenarios in order to argue that the principle of respect for persons informed by culture‐specific ideas of personhood may offer an improved ethical construct for analyzing and guiding medical practice in a globalized and plural world.